Encyclopedia of power - Dowding, Keith M. (Thousand Oaks, Calif. SAGE Publications, 2011)
Covers of the use of power in the social sciences and the complex ways in which power has been used. Provides a reference for debates central to the issues of power in different contexts and for related topics, showing how these disparate topics are related to power.
Keywords: Power (Social sciences) -- Encyclopedias; Electronic books